MAPPING OF CHILDREN'S TUBERCULOSIS INCIDENCE BY COVERAGE OF BCG IMMUNIZATION, MALNUTRITION, AND HOME ENVIRONMENT - Galih Haniin Brillianti; Lucia Yovita Hendrati (Universitas Airlangga, 2022)
Background: Based on the Global Tuberculosis (TB) Report, Indonesia is one of the countries with a triple burden of TB, and TB disease can attack all age groups, including children. East Java Province in 2019 was ranked third in the highest number of pediatric TB cases in Indonesia. Purpose: This study aims to describe the distribution trend of tuberculosis cases in children in East Java Province in 2017-2018 based on BCG immunization coverage, cases of malnutrition, amount of healthy houses, and households with PHBS. Methods: The research design was a descriptive study with a correlation study design. The populations were all districts/cities in East Java Province, with as many as 38 districts. The data analysis technique to describe the trend distribution of tuberculosis in children was the health mapper software on a computer developed by World Health Organization (WHO). Results: The distribution of the incidence of tuberculosis in children in East Java from 2017 to 2018 tends to increase. The city of Surabaya became the area with the highest incidence of tuberculosis in children from 2017 to 2018. Based on a spatial map, most districts or cities with BCG immunization coverage, cases of malnutrition, several healthy homes, and high PHBS households experience tuberculosis incidence in children is high. Conclusion: Based on the map, spatially, districts or cities with high cases of tuberculosis in children mainly occur in areas with cases of malnutrition, the number of healthy home environments, and high coverage of BCG immunization as well.